Penerapan Metode Studi Kasus Pada Mata Pelajaran Agama Islam Dalam Upaya Meningkatkan Pemahaman Siswa Di Upt Sd Negeri 030322 Ujung Teran Kecamatan Tigalingga Kabupaten Dairi - Trisna Wati Lubis; Hadi Saputra Panggaebean; Sakban Lubis (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to improve students' understanding and analytical skills in Islamic Religious Education subjects through the application of the case study method at the UPT SD Negeri 030322 Ujung Teran, Tigalingga District, Dairi Regency. The problem that is the focus of the study is the low understanding and analytical skills of students in Islamic Religious Education learning that still uses conventional methods. This study uses an action research method with a qualitative approach. The subjects of the study were students in grades IV (14 people), V (11 people), and VI (21 people) with a total of 46 students. Data collection was carried out through observation, interviews, documentation, and analytical skills tests. The case study method was applied by presenting real situations relevant to Islamic Religious Education material for students to analyze. The results of the study indicate that the application of the case study method can improve students' understanding of Islamic Religious Education concepts and analytical skills in solving religious problems in everyday life. This study contributes to the development of more contextual and meaningful Islamic Religious Education learning methods for elementary school students.